Preparing for the Certified OpenStack Administrator exam : a complete guide for test takers - Dorn, Matt (Packt Publishing, 2017)
Master the objectives required to pass the Certified OpenStack Administrator exam. About This Book Focuses on providing a clear, concise strategy so you gain the specific skills required to pass the Certified OpenStack Administrator exam Includes exercises and performance-based tasks to ensure all exam objectives can be completed via the Horizon dashboard and command-line interface Includes a free OpenStack Virtual Appliance to practice the objectives covered throughout the book Includes a practice exam to put your OpenStack skills to the test to prove you have what it takes to conquer the live exam Updated for the 2017 exam featuring OpenStack Newton Who This Book Is For This book is for IT professionals, system administrators, DevOps engineers, and software developers with basic Linux command-line and networking knowledge. It's also a great guide for those interested in an entry-level OpenStack position but have limited real-world OpenStack experience. After passing the exam, Certified OpenStack Administrators will prove they have the required skills for the job. What You Will Learn Manage the Keystone identity service by creating and modifying domains, groups, projects, users, roles, services, endpoints, and quotas. Upload Glance images, launch new Nova instances, and create flavors, key pairs, and snapshots. Discover Neutron tenant and provider networks, security groups, routers, and floating IPs. Manage the Cinder block storage service by creating volumes and attaching them to instances. Create Swift containers and set access control lists to allow read/write access to your objects. Explore Heat orchestration templates and create, list, and update stacks. In Detail This book provides you with a specific strategy to pass the OpenStack Foundation's first professional certification: the Certified OpenStack Administrator. In a recent survey, 78% of respondents said the OpenStack skills shortage had deterred them from adopting OpenStack. Consider this an opportunity to increase employer and customer confidence by proving you have the skills required to administrate real-world OpenStack clouds. You will begin your journey by getting well-versed with the OpenStack environment, understanding the benefits of taking the exam, and installing an included OpenStack all-in-one virtual appliance so you can work through objectives covered throughout the book. After exploring the basics of the individual services, you will be introduced to strategies to a...